Corporate information strategy and management : - Applegate, Lynda M. (McGraw-Hill, 2003)
Corporate Information Strategy and Management: Text and Cases 8/e" by Applegate, Austin, and Soule is written for students and managers who desire an overview of contemporary information systems technology management. This new edition examines how information technology (IT) enables organizations to conduct business in radically different and more effective ways. The author's objective is to provide readers with a better understanding of the influence of twenty-first century technologies on business decisions. The 8th edition discusses today's challenges from the point of view of the executives who are grappling with them. This text is comprised of an extensive collection of Harvard Business cases devoted to Information Technology.